Dominant resistance to Bt cotton and minor cross-resistance to Bt toxin Cry2Ab in cotton bollworm from China - Jin, Lin (John Wiley & Sons Ltd, 2013)
Evolution of resistance by insect pests threatens the long-term benefits of transgenic crops that produce insecticidal proteins from Bacillus thuringiensis (Bt). Previous work has detected increases in the frequency of resistance to Bt toxin Cry1Ac in populations of cotton bollworm, Helicoverpa armigera, from northern China where Bt cotton producing Cry1Ac has been grown extensively for more than a decade. Confirming that trend, we report evidence from 2011 showing that the percentage of individuals resistant to a diagnostic concentration of Cry1Ac was significantly higher in two populations from different provinces of northern China (1.4% and 2.3%) compared with previously tested susceptible field populations (0%). We isolated two resistant strains: one from each of the two field-selected populations. Relative to a susceptible strain, the two strains had 460- and 1200-fold resistance to Cry1Ac, respectively. Both strains had dominant resistance to a diagnostic concentration of Cry1Ac in diet and to Bt cotton leaves containing Cry1Ac. Both strains had low, but significant cross-resistance to Cry2Ab (4.2- and 5.9-fold), which is used widely as the second toxin in two-toxin Bt cotton. Compared with resistance in other strains of H. armigera, the resistance in the two strains characterized here may be especially difficult to suppress.